2021
DOI: 10.15548/jt.v28i3.701
|View full text |Cite
|
Sign up to set email alerts
|

Online Lecture During Covid-19 Pandemic from College Students’ Perspective

Abstract: This research aims to analyze the obstacles of online learning during pandemic Covid-19. There have been pros and cons of online lecture during the pandemic due to lack of effectiveness of achieving education goals. However, education is expected to bring an improvement to students to be well-educated generation. To reach the goal, students must comprehend the materials given by lecturers. Yet, there are some problems that college students face during the process of online lecture. These problems became the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Most studies showed that branded online learning tools were provided for public utilization. Like the trend of online learning in the world, most higher education institutions in Indonesia utilize WhatsApp, Google Classroom, Zoom, and Microsoft Teams [8], [34]- [36]. Stakeholders chose the public online tools primarily because of their usability and friendliness to the users.…”
Section: Trends and Stakeholders' Interest In Online Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies showed that branded online learning tools were provided for public utilization. Like the trend of online learning in the world, most higher education institutions in Indonesia utilize WhatsApp, Google Classroom, Zoom, and Microsoft Teams [8], [34]- [36]. Stakeholders chose the public online tools primarily because of their usability and friendliness to the users.…”
Section: Trends and Stakeholders' Interest In Online Learningmentioning
confidence: 99%
“…[7] Zoom, WhatsApp, Google Form, and voice note [35] Microsoft Teams, Zoom, Google Meet [17] Blackboard Collaborate, Webex, Microsoft Teams, Google Meet, and Zoom [34] Edmodo, Google Classroom, WhatsApp, and Zoom [11] SPOT UPI, Google Classroom, Schology, Edmodo, Webex, Moodle, Skype, Kahoot, Quipper, Zoom, WhatsApp group, Google Meet, and Google Duo. [8] Zoom, WhatsApp, Google Classroom, and YouTube [36] Zoom, WhatsApp, Google Classroom, YouTube, and email [55] Zoom, WhatsApp, Google Meet, and other application (not mention) [38] Zoom, WhatsApp, Google Classroom, YouTube, and Telegram [23] Zoom, WhatsApp, Google Meet, and email [40] e-learning, Zoom, WhatsApp, Google Classroom, and YouTube [56] Moodle, Microsoft Teams, Zoom, WhatsApp, Google Meet, and email [57] e-learning fipp, Zoom, and WhatsApp [58] Zoom, WhatsApp, Google Classroom, Google Form, email, YouTube, Quizizz, and Mentimeter [21] Zoom, Google Classroom, SIP, and SPADA (Indonesia MOOC) [39] Zoom, WhatsApp, and Google Classroom [59] Zoom, WhatsApp, Google Classroom, email, and other applications (not mention) [60] Zoom, WhatsApp, Google Classroom, Cisco Webex Meet, and email [61] LMS Uniqbha, Zoom, WhatsApp, Google Classroom Webex, and email.…”
Section: Trends and Stakeholders' Interest In Online Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of prior research that has used the proposed e-learning systems success model (ELS) since it was published in 2017 shows that part of this research used the model's accompanied factors and dimensions to extend new models [8][9][10][11][12][13][14]. The other part of these researches used some aspects of the model to compare it with other models [15][16][17].…”
Section: E-learning Systems Success Model In the Literaturementioning
confidence: 99%